The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1037/tra0000303
|View full text |Cite
|
Sign up to set email alerts
|

Predictive accuracy and factor structure of the Child Report of Posttraumatic Symptoms (CROPS) among adjudicated youth.

Abstract: Overall findings provide moderate support for the utility of the CROPS in accurately identifying previous trauma exposure(s) among adjudicated youth and provide preliminary support for a 14-item version of the CROPS for screening for trauma symptoms in adjudicated youth. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 40 publications
(87 reference statements)
0
11
0
Order By: Relevance
“…Several studies have demonstrated the validity and reliability of the CROPS and the PROPS in general populations [ 61 ]. Additionally, the CROPS has been validated in a sample of juvenile offenders [ 62 ]. The CROPS and the PROPS have been jointly developed so that the CROPS focuses on internal thoughts and feelings, whereas the PROPS focuses on observable behaviors.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have demonstrated the validity and reliability of the CROPS and the PROPS in general populations [ 61 ]. Additionally, the CROPS has been validated in a sample of juvenile offenders [ 62 ]. The CROPS and the PROPS have been jointly developed so that the CROPS focuses on internal thoughts and feelings, whereas the PROPS focuses on observable behaviors.…”
Section: Methodsmentioning
confidence: 99%
“…Elevated scores could also indicate sleep problems (including nightmares) and concentration difficulties. Together, findings from Edner et al (2017) suggest that the abbreviated 14-item CROPS measure could be a viable tool for measuring trauma symptoms among juvenile offenders. However, the CROPS 14-item has yet to validated with an established measure of trauma for children and adolescents.…”
mentioning
confidence: 92%
“…The CROPS 14-item provided improved accuracy in detecting previous trauma exposure among male offenders (61.1% vs. 66.7%) and commensurate detection accuracy for female offenders (66.4%) compared with the CROPS total score. This abbreviated measure also demonstrated solid internal consistency for both male and female offenders, with Cronbach’s alpha coefficients ranging from .86 to .88 (Edner et al, 2017).…”
mentioning
confidence: 96%
See 2 more Smart Citations